Mechanism and Function of the Outer Membrane Channel TolC in Multidrug Resistance and Physiology of Enterobacteria - Zgurskaya, Helen I.; Krishnamoorthy, Ganesh; Ntreh, Abigail; Lu, Shuo (Frontiers in Microbiology, 2011)
TolC is an archetypal member of the Outer membrane Efflux Protein (OEP) family. These proteins are involved in export of peptide and small molecule toxins across the outer membrane of Gram-negative bacteria. Genomes of some bacteria such as Pseudomonas species contain multiple copies of OEPs. In contrast, enterobacteria contain a single tolC gene, the product of which functions with multiple transporters. Inactivation of tolC has a major impact on enterobacterial physiology and virulence. Recent studies suggest that the role of TolC in physiology of enterobacteria is very broad and affects almost all aspects of cell adaptation to adverse enviroments. We review the current state of understanding TolC structure and present an integrated view of TolC function in enterobacteria. We propose that seemingly unrelated phenotypes of tolC mutants are linked together by a single most common condition – an oxidative damage to membranes.